Relevansi Pemikiran Ibnu Khaldun dalam Pembelajaran Sejarah: Systematic Literature Review - Fadila Fadila; Agus Mulyana; Erlina Winarti (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research is entitled “The Relevance of Ibn Khaldun's Thought in History Learning” as for the background of taking the title is Ibn Khaldun is a great scientist figure from Islamic civilization who has great thoughts, especially in history. The purpose of this study is to find out what is the relevance of Ibn Khaldun's thinking in learning history. The research method used by the author is library research (liberary reaseach) by reviewing written sources in the form of journals, books, articles and others related to Ibn Khaldun's thoughts in education using a qualitative approach. This research was conducted on scientific articles in 2014-2023 data obtained from Google Schoolar, Elsiver, and Science Direct articles relevant to the research question. After going through a screening process based on criteria and quality, 15 articles were obtained that qualified to answer the research questions. bstract english version, written using Time New Roman 11pt, italic. Abstract contains research aim/purpose, method, reseach results and conclusion; written in 1 paragraph contains 200 words at most, single space among rows, using past tense sentences. Please consult the English teacher at your school.